Heat of hydration of cement pastes containing high-volume fly ash and silica fume - Watcharapong Wongkeo (2019)
© 2019, Akadémiai Kiadó, Budapest, Hungary. This paper reports the effect of high-volume fly ash (low and high calcium types) with and without silica fume as Portland cement replacement on the heat of hydration of binary and ternary cement mixes. Both low and high calcium fly ash types were used to replace part of Portland cement at 50%, 60% and 70% by mass as binary cement mixes. The combination of fly ash and silica fume at 10% by mass as ternary cement mixes was also studied. The results indicated that low calcium fly ash retarded the rate of heat evolution more than high calcium fly ash at the same cement replacement levels. The total released heat reduction of about 70% can be achieved as Portland cement was replaced up to 70 mass% with low calcium fly ash. Total released heat of high calcium fly ash when compared to low calcium fly ash at 50%, 60% and 70% by mass of Portland cement replacement levels were higher by approximately 35%, 24% and 63%, respectively. The results confirmed that CaO content in fly ash had a significant effect on the hydration reaction of these cement mixes. In ternary cement mixes, in both low and high calcium fly ash, silica fume acted as a nucleation site that results to acceleration in the rate of heat evolution and total released heat more so than binary mix cement pastes, which contributed to the increase in early age compressive strength.